Evaluation of anticancer effects of Asystasia gangetica (Chinese violet) on breast cancer - Juliana, Quek Xinhui (2025)
Breast cancer remains a significant global health challenge especially for women, where its cause can be summed down to being lifestyle or genetic alterations that accelerated the occurrence of breast cancer among women globally. To combat the adverse effects brought on by current breast cancer treatments such as chemotherapy and radiotherapy, alternative medicines in forms of traditional herbs have been under the spotlight as a possible treatment substitute in recent years. In tropical countries such as Africa and Malaysia, plants such as A.gangetica are extensively used as a remedy for asthma or rheumatism. In this research, the anticancer effects of A.gangetica was tested using MCF-7 cells via cell viability and cell proliferation assays. The plant was extracted via maceration using multiple solvents to form fractions, at which further analysis gas chromatography-mass spectrophotometry (GCMS) showed that A.gangetica contains anticancer-related phytochemicals that have been proven to possess anticancer properties via inhibition of cancer mechanisms such as carcinogenesis and malignant development of tumors, such as 6-Chloro-3-ethyl-2-methyl-4-phenylquinoline, Gorgostane, (5.alpha.)-., or .beta.-Sitosterol. Qualitative and quantitative analysis showed the presence of polyphenols, flavonoids, and tannins within the extracts. The extracts were found to have relatively low concentration of flavonoid and tannins, while their polyphenol contents were the opposite. The anticancer effects analysis of the extract fractions was carried out via cell viability and cell proliferation assay using CCK-8, where the MCF-7 cells were treated at 200ug/mL, 100ug/mL, 50ug/mL, and 5ug/mL for 24, 48, and 72 hours. The percentage of cell viability was deduced from the absorbances of the wells at 450nm, where it was found that DCM at 200ug/mL was the most effective, bringing cell viability of the MCF-7 cells down to 74.9%. The exceptionally high cell viability percentages detected in other extracts were suspected to be due to the presence of carcinogenic compounds found within the extracts at higher concentration. To ensure validity of the research result, DCM extracts require further purification and repeats in cell viability assays. Further research and experiments are required to verify the anticancer effects of A.gangetica.